Las Spin-Off universitarias. Elementos para un debate necesario (Perspectivas de las Ciencias Económicas y Jurídicas, 2022)
The university spin-off has gained a strong relevance in recent years. We propose to present the main elements for the public debate discussing topics such as the motivations for the birth of these companies, university policy and technology transfer offices and the architecture of the university action for the promotion of spin-offs. Without neglecting the main university functions, the facet of promoting development through the constitution of new companies can represent a powerful tool to improve academic performance, but above all, to influence the path of progress of our society.